From genomes to genitalia: ecological speciation in sulfide spring fishes - Greenway, Ryan (Kansas State University, 2019)
As closely related lineages adapt to habitats characterized by divergent sources of natural selection, the accumulation of different adaptations can lead to reproductive isolation and a reduction in gene flow between those lineages, facilitating the speciation process. Organisms living in extreme environments – habitats characterized by physiochemical stressors lethal to most forms of life – provide ideal systems for the study of adaptive divergence and ecological speciation. Extreme environments exhibit clearly defined selective regimes, enabling hypothesis-driven tests of the effects of physiochemical stressors on trait evolution across levels of biological organization. Additionally, lineages closely related to those found in extreme environments often occur in adjacent, benign habitats, facilitating studies of divergence between habitats. I used a unique system in which evolutionarily independent populations of livebearing fishes (family Poeciliidae) have colonized extreme environments in the form of freshwater springs rich in the naturally occurring toxicant hydrogen sulfide (H2S) to address three major objectives. (1) I determined whether female fish use adaptive trait differences between populations in different habitats as signals for making mating decisions that contribute to reproductive isolation between populations from different habitat types. (2) I measured variation in female and male genitalia among populations to determine if divergence in genital traits between habitat types could facilitate the evolution of reproductive isolation at early stages of ecological speciation. (3) I characterized adaptive divergence and reproductive isolation between population pairs of three distantly related species that occur in the same sulfide spring and adjacent non-sulfidic stream to identify common patterns of adaptive divergence across levels of biological organization. Using a combination of field and laboratory experiments in conjunction with genomic tools, I found that (1) female fish prefer aspects of male body shape indicative of local adaptation, (2) female and male genitalia coevolve within populations and diverge among populations in different habitat types during the early stages of speciation, potentially contributing to reproductive isolation between populations, and (3) convergent patterns of adaptive divergence and ecological speciation can be the result of unique genomic mechanisms in distantly related species. Overall, my dissertation research links evolutionary changes across multiple levels of biological organization in order to understand the formation of new species and the predictability of evolution driven by natural selection.
Keywords: Ecological speciation; Reproductive isolation; Local adaptation; Ecological genomics; Poecilia mexicana; Hydrogen sulfide